Axilary Block Ultrasound Guiding in Patient with Pseudoaneurysm Regio Brachii Sinistra pro Repair Pseudoaneurysm - Heri Dwi Purnomo; Emmanuel Kurnia Kasmantino (Journal of Anaesthesia and Pain, 2022)
Background: An aneurysm may be a true aneurysm or a pseudoaneurysm. Pseudoaneurysm is defined as a defect in the arterial wall, making a connection between the lumen and the extraluminal space. The main etiology of brachial artery pseudoaneurysm is incidental arterial puncture during venous cannulation for hemodialysis.Case:: Anesthetic management was performed on a female patient 56 years old, body weight 45 kg, height 150 cm. The patient had other comorbidities such as hypertension, diabetes mellitus, chronic renal kidney with a diagnosis of left brachial pseudoanuerysm. Pro Pseudoanurysm repair surgery. The anesthetic technique uses axillary peripheral nerve block with ultrasound guiding. The duration of surgery is ± 120 minutes. After the operation, the patient was treated in the hospital ward.Conclusion: Choosing the most appropriate anesthetic technique for patients with renal impairment is necessary to maintain normovolemia and normotension in order to avoid unexpected complications. Using regional anesthetic technique for sympathetic nerve block may be favorable in these patients. With ultrasound guiding, the incidence of failure is lower, the time required is shorter, the latency is shorter, the blockade is longer, and the risk of accidental vascular puncture is lower so that vascular lesions are less likely.